1993
DOI: 10.1038/ng0293-157
|View full text |Cite
|
Sign up to set email alerts
|

CFTR expression is regulated during both the cycle of the seminiferous epithelium and the oestrous cycle of rodents

Abstract: Severely reduced fertility is a common finding in cystic fibrosis (CF). We used in situ hybridization to examine the cell-specific expression of CFTR in the reproductive organs of rodents. In males CFTR mRNA is found in the round spermatids (spermatogenic stages V-X) and in the principal cells that line the initial segment of the epididymis. In both the testis and the epididymis, CFTR expression is developmentally regulated suggesting that the defect in the genital tract of male CF patients is of developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 43 publications
6
84
0
4
Order By: Relevance
“…Such a proposition is not untenable in view of the recent reports that germ cells in vitro activate the phosphatidyl inositol pathway (probably through ATP release) in rat Sertoli cells (Welsh & Ireland, 1992). Furthermore, the detection of cystic fibrosis transmembrane conductance (CFTR) gene expression in germ cells in vivo (Trezise et al 1993) gives added weight to this hypothesis, for there is now a growing body of evidence that CFTR mediates ATP efflux in a number of cell systems (Rotoli et al 1996;Cantiello et al 1997). Alternatively, ATP may be released by the Sertoli cells in the testis and act on the same or adjacent Sertoli cells to control fluid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Such a proposition is not untenable in view of the recent reports that germ cells in vitro activate the phosphatidyl inositol pathway (probably through ATP release) in rat Sertoli cells (Welsh & Ireland, 1992). Furthermore, the detection of cystic fibrosis transmembrane conductance (CFTR) gene expression in germ cells in vivo (Trezise et al 1993) gives added weight to this hypothesis, for there is now a growing body of evidence that CFTR mediates ATP efflux in a number of cell systems (Rotoli et al 1996;Cantiello et al 1997). Alternatively, ATP may be released by the Sertoli cells in the testis and act on the same or adjacent Sertoli cells to control fluid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of CFTR in the vas deferens has been controversial. Using in situ hybridization, Trezise et al (1993) did not detect Cftr mRNA in the rat vas deferens, whereas Patrizio & Salameh (1998) reported a strong signal in the human vas deferens. Pietrement et al (2008) reported that CFTR co-localized with aquaporin 9 and NHERF1 in the apical membrane of rat epididymis and vas deferens, but they only show results for the epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…These included consensus sites in PR3 for C\EBP, and in PR4 for CRE, AP-1 and ER. CFTR is known to show hormonal regulation of expression during the oestrous cycle of rodents [10]. However, the ER site in 164 was a single half-site, with no sites in the adjacent DNA ; it was therefore thought unlikely to be important and was not investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of rodent tissues by in situ hybridization have shown gradients of CFTR expression in the intestine along both the crypt-villus and proximal-distal axes [9]. CFTR expression is also hormonally regulated in the rodent uterus and shows stage-specific expression during spermatogenesis [10]. Hence the CFTR gene exhibits a complex, tightly regulated pattern of expression, yet relatively little is known of the complex mechanisms underlying this.…”
Section: Introductionmentioning
confidence: 99%